2010
DOI: 10.1128/jcm.01944-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of the O122 Pathogenicity Island in Typical and Atypical Enteropathogenic Escherichia coli Strains

Abstract: The presence of the pathogenicity island (PAI) O122 genes, efa1 (lifA), sen, pagC, nleB, and nleE, in typical and atypical enteropathogenic Escherichia coli (EPEC) strains was investigated. The simultaneous occurrence of all genes was statistically associated with diarrhea due to atypical EPEC. Detection of the complete PAI O122 could aid in the identification of potential pathogenic strains of atypical EPEC.Enteropathogenic Escherichia coli (EPEC) and Shiga toxin (Stx)-producing E. coli (STEC) are important h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
3
24
3
5
Order By: Relevance
“…These results differ from those reported by Vieira, where complete PAI O-122 was found in 32.5% of EPEC strains isolated from patients with diarrhea and was more prevalent in t-EPEC than in a-EPEC (48.9% versus 17.8%, respectively). Considering t-EPEC and a-EPEC strains together, the presence of complete PAI O-122 was similar among strains isolated from diarrhea (8.6%) and control (9.6%), different than the data reported by Vieira where EPEC and a-EPEC strains with complete PAI O-122 were significantly associated with diarrhea (32.5% and 22.4%) than control strains (10.5% and 6.5) respectively (Vieira et al, 2010). …”
Section: Discusioncontrasting
confidence: 77%
See 1 more Smart Citation
“…These results differ from those reported by Vieira, where complete PAI O-122 was found in 32.5% of EPEC strains isolated from patients with diarrhea and was more prevalent in t-EPEC than in a-EPEC (48.9% versus 17.8%, respectively). Considering t-EPEC and a-EPEC strains together, the presence of complete PAI O-122 was similar among strains isolated from diarrhea (8.6%) and control (9.6%), different than the data reported by Vieira where EPEC and a-EPEC strains with complete PAI O-122 were significantly associated with diarrhea (32.5% and 22.4%) than control strains (10.5% and 6.5) respectively (Vieira et al, 2010). …”
Section: Discusioncontrasting
confidence: 77%
“…However, its association with diarrhea is controversial (Afset et al, 2006). Vieira et al, have shown that typical and atypical EPEC strains may harbor a complete ( pagC, senA, nleB, nleE and lifA/efa-1 all together) or incomplete PAI O-122; a strong association between the presence of a complete PAI O-122 and diarrhea was observed only in a-EPEC strains (Vieira et al, 2010). It is unknown if incomplete PAI O-122 could also be associated with diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…However, group C isolates from four other sheep flocks had MLVA profiles (6-3-0-8-3-4-1 or 6-3-0-8-3-7-1) previously described for human E. coli O26, but these isolates were from patients infected in Brazil (39). Although the group C isolates lacked typical EHEC genes such as stx, ehxA, and espK, their virulence gene profile (eae, nleB, efa1, lpfA R141 , and lpfA O113 ) indicates that these E. coli O26:H11 isolates cannot be considered nonpathogenic to humans (1,16,57).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, yjaA was absent from all isolates. Previous clinical studies have shown that the presence of OI-122 genes and absence of yjaA were associated with diarrhea in patients infected with aEPEC (1,57). Recently, a close relationship between the presence of the nleB gene and highly virulent EHEC and EPEC strains was found (16).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation